2023
DOI: 10.3390/app13074597
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Virtual Reality-Based Early Postoperative Rehabilitation after Total Knee Arthroplasty: A Systematic Review with Meta-Analysis of Randomized Controlled Trials

Abstract: Virtual reality-based rehabilitation (VRBR) is being used in rehabilitation after total knee arthroplasty (TKA). This meta-analysis assesses the effect of immediate and/or maintained effect of VRBR (alone or in combination with conventional therapy (CT) in TKA recovery. To perform this meta-analysis, we searched in PubMed, SCOPUS, WOS, CINAHL, and PEDro until 5 February 2023. We included randomized controlled trials that assessed the effect of VRBR in improving knee pain and function, dynamic balance, range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 80 publications
1
3
1
Order By: Relevance
“…However, no differences were found between the experimental group and the control group for the range of motion measured by short-term ROM. Our results contrast those of other authors, who reported a significant improvement in the experimental groups compared to the control between 2 weeks and 3 months after surgery [ 38 , 39 ].…”
Section: Discussioncontrasting
confidence: 99%
“…However, no differences were found between the experimental group and the control group for the range of motion measured by short-term ROM. Our results contrast those of other authors, who reported a significant improvement in the experimental groups compared to the control between 2 weeks and 3 months after surgery [ 38 , 39 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The same results were found by Olbrecht et al, reinforcing to the fact that pain is mostly diminished by distraction and redirection [22]. Many studies support the theory that distraction leads to most of the analgesia provided by VR [23]. Whether it works directly or indirectly on signaling pathways of pain, attention, or emotion, it is clear that the affective component of pain is influenced by distraction via VR use [23,24].…”
Section: Discussionsupporting
confidence: 69%
“…Many studies support the theory that distraction leads to most of the analgesia provided by VR [23]. Whether it works directly or indirectly on signaling pathways of pain, attention, or emotion, it is clear that the affective component of pain is influenced by distraction via VR use [23,24]. Another way of influencing painful sensations with VR is pain control, wherein the subject is invited to control the pain while immersed in the virtual reality.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The application of VR-based rehabilitation in Orthopedic surgery, especially in THR/TKR, has noticeably and significantly risen [18,19]. Several VRbased protocols have been proposed for rehabilitation following TKR and THR [16,[18][19][20]. However, none of the articles examined the effectiveness of VR-based interventions for symptoms of stress, anxiety, and depression in patients with OA after THR or after TKR.…”
Section: Introductionmentioning
confidence: 99%